Fundamental Issues in Manufacturing Photovoltaic Modules Beyond the Current Generation of Materials. (12th January 2012) - Alapatt, G. F.; Singh, R.; Poole, K. F.
Abstract : Many methods to improve the solar cell's efficiency beyond current generation of bulk and thin film of photovoltaic (PV) devices have been reported during the last five decades. Concepts such as multiple exciton generations (MEG), carrier multiplication (CM), hot carrier extraction, and intermediate band solar cells have fundamental flaws, and there is no experimental evidence of fabricating practical higher efficiency solar cells based on the proposed concepts. To take advantages of quantum features of nanostructures for higher performance PV devices, self-assembly-based bottom-up processing techniques are not suitable for manufacturing due to inherent problems of variability, defects, reliability, and yield. For processing nanostructures, new techniques need to be invented with the features of critical dimensional control, structural homogeneity, and lower cost of ownership as compared to the processing tools used in current generations of bulk and thin-film solar cells.